2018
DOI: 10.1177/0034355217747690
|View full text |Cite
|
Sign up to set email alerts
|

A Needs Driven Model of Workplace Social Effectiveness in Adults With Disabilities

Abstract: I've learned that people will forget what you said, people will forget what you did, but people will never forget how you made them feel.-Carl W. Buehner One of the most central, constant, and marginalizing discrepancies between people with and without disabilities is the opportunity to work. Unemployment rates are nearly two and a half times higher for people with disabilities than for people without disabilities (U.S. Bureau of Labor Statistics, 2017), a dismal discrepancy that has become the norm (Stapleton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 93 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…There is also good concurrent validity between the PMI and Paykel's (1974) Suicidal Ladder (r = -.539) (Seager et al, 2014). Phillips et al, (2018) found good concurrent validity with PsyCap (a measure of an appealing personality; r = .687) and the Subjective Happiness Scale (r = .689). The norm score for the PMI is around 3.3 (0.8) for men and women combined.…”
Section: Methodsmentioning
confidence: 91%
“…There is also good concurrent validity between the PMI and Paykel's (1974) Suicidal Ladder (r = -.539) (Seager et al, 2014). Phillips et al, (2018) found good concurrent validity with PsyCap (a measure of an appealing personality; r = .687) and the Subjective Happiness Scale (r = .689). The norm score for the PMI is around 3.3 (0.8) for men and women combined.…”
Section: Methodsmentioning
confidence: 91%
“…Data were only included when values were reported across all three longitudinal measures. Five other studies have been published from this dataset that focus on other constructs collected at single time points, with two being instrument validation studies (Fleming et al, 2020; Fry et al, 2020; Phillips et al, 2018; Phillips, Iwanaga, et al, 2021; Phillips, Fleming, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%